THE RELATHIONSHIP OF NITRATE, PHOSPHATE AND SILICATE CONCENTRATION WITH PLANKTONIC DIATOMS ABUNDANCE IN TELUK BUO WATERS BUNGUS TELUK KABUNG DISTRICT PADANGCITY WEST SUMATERA - Syawfy Luthfiandra; Irvina Nurrachmi; Efriyeldi Efriyeldi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT The aims of study was to analyze the relationship of planktonic diatoms abundance with the concentration of nitrate, phosphate and silicate from the Teluk Buoof waters. Placement of sampling location using purposive sampling that was by dividing the research location into four station with 3 point of sampling at each station in Teluk Buo waters which serve as research location. Field sampling was conducted in March 2018 and the observation and identification of planktonic diatoms were conducted in Marine Biology Laboratory of the Fisheries and Marine Faculty of Riau University. The results showed that nitrate concentration in Teluk Buo waters ranged from 0.0125 - 0.0333 mg/l, phosphate concentration ranged from 0.0413 - 0.0841 mg/l,and silicate concentrations ranged from 0.0228 - 0.0354 mg/l. Nine species of plantonic diatoms were finded in Teluk Buo of waterswasBiddulphia sp, Isthimisp, Coscinodiscus sp, Flagilaria sp, Nitzschia sp, Navicula sp, Aulacoseira sp, Bacillaria sp, dan Cymbella sp. The average abundance of diatoms in these waters 181-250 ind/l. Regression test results, nitrate correlation value with diatomic abundance shows a relationshipwas positive, while the value of phosphate and silicate correlation with diatomic abundance shows a relationshipwas negative. Key word : Planktonic Diatoms, Nitrate, Phosphate and Silicate, Teluk Buo Waters